Localization and velocity tracking of human via 3 IMU sensors - Yuan, Qilong (2016)
In sports training and exercises like walking and jogging, the velocity and position of the exercise people is very crucial for motion evaluation. A simple wearable system and corresponding method for velocity monitoring using minimal sensors can be very useful for daily use. In this work, a velocity tracking and localization method using only three IMU sensors is introduced. The three sensors are located at the right shank, right thigh and the pelvis to measure the kinematics of the lower limbs. In the method, a reference root point on the pelvis is chosen to represent the velocity and location of the person. Through acceleration fine tuning algorithm, the acceleration data is refined and combined with the velocity calculated from body kinematics to get a drift-free and accurate 3D velocity result. The location of the person is tracked based on this velocity estimation and the limb kinematic subsequently. The benchmark study with the commercial optical reference shows that the error in velocity tracking is within 0.1 m/s and localization accuracy is within 2% in both normal walking, jogging and jumping. Due to the conveniences of the small-size wearable IMU sensors, this proposed velocity tracking and localization method is very useful in everyday exercises both indoor and outdoor.